A collective trigger for widespread planetesimal formation revealed by accretion ages - James F.J. Bryson; Hannah R. Sanderson; Francis Nimmo; Sanjana Sridhar; Gregory A. Brennecka; Yves Marrocchi; Jason P. Terry (Earth and Planetary Science Letters, 2026)

Magnetization and age of ca. 544 Ma syenite, eastern Canada: Evidence for renewal of the geodynamo - Tinghong Zhou; Mauricio Ibañez-Mejia; Richard K. Bono; Rory D. Cottrell; Wouter Bleeker; Kenneth P. Kodama; Wentao Huang; Eric G. Blackman; Francis Nimmo; Aleksey V. Smirnov; John A. Tarduno (Earth and Planetary Science Letters, 2024)

Exploring the potential of topsoil pellets to improve native seedling establishment on degraded agricultural land - Thomas P. Munro; Todd E. Erickson; Dale G. Nimmo; Frederick A. Dadzie; Miriam Muñoz-Rojas; Jodi N. Price (Plant and Soil, 2024)
Background and aims Agricultural activities can degrade soils and promote weeds, posing challenges to native species restoration. In agricultural restoration, removing contaminated topsoil is a method designed to reduce elevated soil nutrients caused by fertilisation. This strategy targets weed control by eliminating both aboveground weeds and their soil seed bank before direct seeding. However, it also diminishes native soil seed banks and beneficial soil microbes. We investigated the potential of fresh topsoil pellets containing seeds to improve seedling performance in a degraded grassy woodland where topsoil had been removed. Methods We tested various pellet recipes, including one using commercial ingredients and three with different topsoil proportions (30%, 50%, and 70%). The study was conducted in a degraded grassy woodland in southeastern Australia, where topsoil was removed for restoration. We explored the effect of these pellet varieties on seedling emergence and growth of six native species common in this community, as well as microbial activity in the soil surrounding the seedlings. Results Pellets significantly improved the emergence of Chrysocephalum apiculatum , providing evidence of their effectiveness. However, pellets significantly reduced Arthropodium milleflorum and Glycine tabacina emergence. Linum marginale and Rytidosperma caespitosum emergence remained unaffected by pellets . One species, Bothriochloa macra, had insufficient emergence for analysis. The microbial activity of the soil surrounding Rytidosperma caespitosum seedlings was significantly improved by pellets, with no significant effects observed for other species. Conclusion Our results demonstrate that topsoil pellets improved the emergence of one native species, but reduced emergence for two others, indicating species-specific responses to pelleting.

Cowpea mild mottle virus, a sometimes problem for French bean crops - C. Gambley; P. Nimmo; D. Persley; V. Steele; M. Sharman; P. Campbell (Australasian Plant Pathology, 2022)
A carlavirus, closely related to cowpea mild mottle virus (CPMMV) and spread by silverleaf whitefly (SLW) was reported affecting fresh market beans in a major Australian growing district in 2016. Further investigations of this virus were completed through regular surveys of crops, weeds and SLW in this district from 2016–2019. Sequencing of the 3'end of the virus genome from a range of samples detected four variants, referred to as CPMMV:A:FB5288 and CPMMV:A:S1 to S3. The distribution of these four variants in survey samples showed the dominant variant in French bean crops as CPMMV:A:FB5288. The surveys also showed disease impacts were limited to autumn and varied over time. This variation is attributed to the influence of rainfall on adult insect vector levels. The experimental host range of CPMMV:A:FB5288 was shown to be limited to the Phaseoleae plant tribe and included the Australian native species, Glycine canescens . French bean varieties showed a range of susceptibilities to this dominant sequence variant from highly tolerant to very susceptible. The tolerant varieties provide the local industry with some options for disease management where previously there were none. Genetic diversity studies further highlight the need for taxonomic reform of the species referred to as CPMMV.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effects of sprint interval training on ectopic lipids and tissue-specific insulin sensitivity in men with non-alcoholic fatty liver disease - Jack A. Sargeant; Stephen Bawden; Guruprasad P. Aithal; Elizabeth J. Simpson; Ian A. Macdonald; Mark C. Turner; Jessica Cegielski; Kenneth Smith; James L. Dorling; Penny A. Gowland; Myra A. Nimmo; James A. King (European Journal of Applied Physiology, 2018)

Differential Accumulation of Mercury and Selenium in Brown Trout Tissues of a High-Gradient Urbanized Stream in Colorado, USA - S. J. Herrmann; D. R. Nimmo; J. S. Carsella; L. M. Herrmann-Hoesing; J. A. Turner; J. M. Gregorich; B. D. Vanden Heuvel; R. B. Nehring; H. P. Foutz (Archives of Environmental Contamination and Toxicology, 2016)

Methicillin-susceptible, non-multiresistant methicillin-resistant and multiresistant methicillin-resistant Staphylococcus aureus infections: a clinical, epidemiological and microbiological comparative study - W. J. Munckhof; G. R. Nimmo; J. Carney; J. M. Schooneveldt; F. Huygens; J. Inman-Bamber; E. Tong; A. Morton; P. Giffard (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Toxicity of Aroclor® 1254 and its physiological activity in several estuarine organisms - D. R. Nimmo; D. J. Hansen; J. A. Couch; N. R. Cooley; P. R. Parrish; J. I. Lowe (Archives of Environmental Contamination and Toxicology, 1975)